2012
DOI: 10.1055/s-0031-1299731
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of Cardiopulmonary Function in Newborns with Congenital Diaphragmatic Hernia Using Lung Function Parameters and Hemodynamic Management

Abstract: Measurements of lung function parameters and adaptation of mechanical ventilation to the degree of pulmonary hypoplasia and additional therapy with PGE1 may help to improve the outcome in CDH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Several working groups have reported FRC and LCI outcomes in healthy infants and infants with CF obtained with this method . Moreover, this equipment together with this software package have been used for the evaluation of lung function in preterm infants, infants with congenital diaphragmatic hernia and ventilated infants and children . Therefore, our findings have broad implications not only for ongoing and future studies, but also for the interpretation of existing data.…”
Section: Discussionmentioning
confidence: 82%
“…Several working groups have reported FRC and LCI outcomes in healthy infants and infants with CF obtained with this method . Moreover, this equipment together with this software package have been used for the evaluation of lung function in preterm infants, infants with congenital diaphragmatic hernia and ventilated infants and children . Therefore, our findings have broad implications not only for ongoing and future studies, but also for the interpretation of existing data.…”
Section: Discussionmentioning
confidence: 82%
“…Echocardiographic markers for PH used in this study include ductal flow velocities and flow patterns and mean pulmonary arterial pressures in relation to systemic blood pressures and classified as suprasystemic when mean PAP > systemic blood pressure +10 mm Hg (26). An observational study conducted by Hofmann et al (72) reported that use of PGE1 in addition to circulatory management with catecholamines in two of their patients with CDH-PH relieved and stabilized right ventricular function. Although these studies reported on common echocardiographic markers of PH and LV dysfunction parameters, it is notable that none of the cited studies assessed RV function.…”
Section: Outcome Measures To Assess Response To Pge1mentioning
confidence: 99%
“…However, babies born with CDH exhibit life-threatening pulmonary hypertension that needs to be resolved before surgery. Lung-protective ventilator strategies or “gentle ventilation”, extracorporeal membrane oxygenation (ECMO), and cardiopulmonary pre-operative stabilization are strategies currently used to tackle hypertension and improve patient outcomes [ 211 , 212 , 213 ].…”
Section: Congenital Lung Malformationsmentioning
confidence: 99%